Physical Activity in Adolescent Females with Type 1 Diabetes - Bahareh Schweiger; Georgeanna Klingensmith; Janet K. Snell-Bergeon (Hindawi Limited, 2010)
Objective. We sought to identify amount of physical activity and relationship of physical activity to glycemic control among adolescent females 11 to 19 years of age with type 1 diabetes mellitus (T1DM). We also sought to evaluate associations of age and ethnicity with physical activity levels. Research Design and Methods. Adolescent females ages 11-19 years (n=203) were recruited during their outpatient diabetes appointment. Physical activity was obtained by self-report and was categorized as the number of days subjects had accumulated 60 minutes of moderate-to-vigorous physical activity during the past 7 days and for a typical week. Results. Girls reported being physically active for at least 60 minutes per day on 2.7±2.3 days in the last week, and on 3.1±2.2 days in a typical week. A greater number of physically active days in a typical week were associated with lower A1c (P=.049) in linear regression analysis. Conclusion. Adolescent females with T1DM report exercising for at least 60 minutes about 3 days per week, which does not meet the international recommendations of 60 minutes of moderate-to-vigorous activity per day. It is particularly important that adolescent girls with T1DM be encouraged to exercise since a greater number of physically active days per week is associated with better glycemic control.